The nucleotide exchange factors of Hsp70 molecular chaperones - Bracher, Andreas; Verghese, Jacob (Frontiers in Molecular Biosciences, 2015)
Molecular chaperones of the Hsp70 family form an important hub in the cellular protein folding networks in bacteria and eukaryotes, connecting translation with the downstream machineries of protein folding and degradation. The Hsp70 folding cycle is driven by two types of cochaperones: J-domain proteins stimulate ATP hydrolysis by Hsp70, while nucleotide exchange factors (NEFs) promote replacement of Hsp70-bound ADP with ATP. Bacteria and organelles of bacterial origin have only one known NEF type for Hsp70, GrpE. In contrast, a large diversity of Hsp70 NEFs has been discovered in the eukaryotic cell. These NEFs belong to the Hsp110/Grp170, HspBP1/Sil1 and BAG domain protein families. In this short review we compare the structures and molecular mechanisms of nucleotide exchange factors for Hsp70 and discuss how these cochaperones contribute to protein folding and quality control in the cell.